Effect of Organic Planting Media on the Growth of Purslane (Portucala oleracea L.) Seedling - F. Deru Dewanti; Sukendah; Puji Lestari Tarigan; Yonny Koentjoro (Future Science, 2022)
Purslane is an annual plant that has various benefits. This plant contains omega 3 which is equivalent to other types of vegetables. So far, purslane is still considered a weed, so it doesn't have a cultivation technique to get the results. This study aims to obtain a combination of planting media for the growth of purslane. This research is the beginning to increase the purslane omega 3 content. Because genetic factors and environmental conditions can affect the growth and development as well as the chemical content of plants. The experimental design used a completely randomized design (CRD). The planting media used were: soil, soil + husk charcoal, soil + compost, and soil + husk charcoal + compost. The treatment was repeated 4 times, so there are 12 observation units. Observations were made on the number of leaves and the number of branches. The results showed that the combination of soil+compost gave the best effect on the number of leaves and the number of branches of the purslane seedling